The societal challenge of schooling the girls from East African pastoralists: confronting narratives and practices - (:unkn) unknown (My University, 2018)
The article examines the challenges of secondary school enrollment for girls from pastoral populations in East Africa. Based on fieldwork among the Maasai of Tanzania, it confronts the different narratives and educational practices of the various stakeholders : the Maasai themselves, whose attitudes towards schooling, especially secondary schooling for girls, differ – depending in particular on their commitment to pastoral activities, their link to Maasai culture and their religion – teachers and people in charge of education who promote the education for girls, such as the members of a Christian church who implemented and finance a private secondary school for young girls of pastoralist whose parents refuse to send them to school. The ethnography of this particular school constitutes a privileged framework for the analysis of these different postures and then, reducing the focus to pupils, the one of the identity of girls enrolled.
Keywords: African Research